Effects of Arbuscular Mycorrhizal Fungi on the Growth of Wheat Plant - Himedah Fheel Alboom; Mabroukah Khalleefah; Najat Mansour; Abdulmunem Abounqab (AlQalam Journal of Medical and Applied Sciences, 2024)
Mycorrhiza is a symbiotic association between a green plant and a fungus. The current study was conducted to assess the effect of inoculation with Arbuscular Mycorrhizal Fungi (AMF) on the growth of seeds of the wheat plant. Triticum aestivum, which is one of the plants that host the fungus, was studied by calculating the wet weight and dry weight of both the root system and the shoot system. In this experiment, roots colonized with AMF were used as a source of injection. Wheat seeds were injected with these roots and compared with other seeds without control injection. The injected plants and uninfected plants were allowed to grow for a period of 75 days. During this period, the plants were harvested over three periods 25, 50, and 75 days. Through this experiment, it was found that AMF have a high efficacy on the growth of the wheat crop, through a positive effect on the growth of the seeds of this host plant. Such studies on AMF are still rare in Libya, so we tried to follow up the previous studies, so we studied this kind of coexistence with this economically important agricultural crop in Libya and the world. تم دراسة تأثير التسميد بفطريات الميكوريزا الشجرية على نمو بذور نبات القمح وهو أحد النباتات التي تتعايش مع الفطر وذلك من خلال حساب الوزن الرطب والوزن الجاف لكل من المجموع الجذري والمجموع الخضري حيث أجريت تجربة أصص داخل البيت الزجاجي في مدينة الزاوية وفي هذه التجربة تم استخدام الجذور المستعمرة بفطريات الميكوريزا كمصدر للحقن وتم حقن بذور القمح بهذه الجذور ومقارنتها ببذور أخرى بدون حقن وتركت النباتات المحقونة والنباتات غير المحقونة تنمو لمدة (75) يوماً وخلال هذه الفترة تم حصاد النباتات على ثلاث فترات (25، 50، 75) يوماً ومن خلال هذه التجربة وجد أن فطريات الميكوريزا لها فاعلية عالية على نمو محصول القمح وذلك من خلال التأثير الإيجابي على نمو بذور هذا النبات العائل. إن مثل هذه الدراسات على فطريات الميكوريزا لا تزال نادرة في ليبيا، لذلك حاولنا متابعة الدراسات السابقة، فدرسنا هذا النوع من التعايش مع هذا المحصول الزراعي المهم اقتصاديا في ليبيا والعالم